2019
DOI: 10.1186/s13048-018-0477-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of serum exosomal miR-375 and miR-1307 enhance the diagnostic power of CA125 for ovarian cancer

Abstract: BackgroundOvarian cancer (OC) is associated with high mortality in gynecological oncology; this is mainly due to the low diagnosis rate. Exosomal miRNA has demonstrated potential as a tumor biomarker. We aimed to explore the diagnostic potential of serum exosomal miR-1307 and miR-375 for OC.MethodsThe first six candidate miRNAs were selected from the previous literature. The relative quantification of qRT-PCR was used to screen for the stability of exosomal miRNAs, followed by validation of the cohort. ROC ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 54 publications
(51 reference statements)
1
50
0
Order By: Relevance
“…In addition, several previous studies have shown that stable circulating miRNAs play an increasingly important role in the diagnosis of OC [9][10][11][12][13][14][15]. However, to our knowledge, few reports have described miRNA levels in exosomes isolated from the plasma of OC patients [16][17][18][19]. Tissue miRNAs present poor stability, but exosomal miRNAs in serum are thought to be more stable [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several previous studies have shown that stable circulating miRNAs play an increasingly important role in the diagnosis of OC [9][10][11][12][13][14][15]. However, to our knowledge, few reports have described miRNA levels in exosomes isolated from the plasma of OC patients [16][17][18][19]. Tissue miRNAs present poor stability, but exosomal miRNAs in serum are thought to be more stable [28].…”
Section: Discussionmentioning
confidence: 99%
“…As we demonstrated, transmission electron microscopy revealed that the clusters isolated from serum were round or oval membrane vesicles largely between 30 and 100 nm in size and were homogeneous in appearance, suggesting that these vesicles were exosomes. Previous studies have also shown the significance of detecting exosomes using immunoblotting against CD63 and electron microscopy [16,21,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking these results together with our previous observations that miR-375 is present in MCC cell line conditioned medium, in sera of preclinical xenotransplantation animal models and in sera of MCC patients [10] suggest, miR-375 may rather serve intercellular than intracellular signaling in MCC. Indeed, miR-375 was recently characterized as an exosomal shuttle miRNA [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from miR-193a-5p, the deregulated plasma levels of which were also reported in recurrent platinum resistant OC patients [146] , the improvement of the diagnostic power of CA125 and HE4 for OC was also shown to be mediated by serum exosomal miR-375 and miR-1307. Su et al [151] detected that both miR-375 and miR-1307 were significantly up-regulated in serum exosomes of OC compared with ovarian benign and healthy groups. Notably, exosomal miR-375 correlated with lymph node metastasis of OC [151] .…”
Section: Circulating Mirnas In Metastasesmentioning
confidence: 99%